The Effect of Fuel Electrode Roughness On the Properties of Plasma Sprayed Solid Oxide Cells. (30th May 2017) - Kuhn, Joel; Gupta, Mohit; Kesler, Olivera; Björklund, Stefan
Abstract : Solid oxide cell electrolytes fabricated by atmospheric plasma spraying are frequently found to have nonzero gas leak rates. Electrode surface roughness is known to have an influence on electrolyte leak rates. A jet of high velocity air, produced with an air knife, was aimed at the plasma plume during fuel electrode deposition to reduce the surface roughness prior to electrolyte deposition. The resulting fuel electrode masses, electrode compositions, and electrode surface roughnesses were measured for varying air knife inlet pressures. Surface asperity populations and maximum heights were significantly reduced using air knife pressures of > 6 bar at the expense of deposition efficiency. The distribution of surface gradients was also improved with the use of the air knife, but some regions with steep gradients still remained in surfaces prepared with an air knife pressure of 8 bar.